2018
DOI: 10.1111/tid.12858
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Clostridium difficile infection in intestinal transplant recipients during the first year post‐transplant

Abstract: Proton pump inhibitor administration might be protective for CDI in ITR. Risks factors for CDI might be different in ITR compared to other populations; anatomical differences and medications administered in the post-transplantation period may affect intestinal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In contrast, a previous nested case‐control study comparing 62 adult allogeneic HCT recipients with 123 controls reported that recipients receiving PPIs were less likely to have CDI (OR 0.29, 95% CI 0.11‐0.78) . Similarly, a single‐site pediatric study comparing 20 SOT recipients with CDI and 35 controls found that acid blockade had a protective effect (OR 0.13, 95% CI: 0.02‐0.78), and a pediatric study in intestinal transplant recipients that compared 29 cases with 87 controls found that PPIs were associated with lower rates of CDI (OR 0.06, 95% CI: 0.007‐0.52) . Findings from these studies may have been limited by small sample size, timing of PPI therapy, or other confounders.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, a previous nested case‐control study comparing 62 adult allogeneic HCT recipients with 123 controls reported that recipients receiving PPIs were less likely to have CDI (OR 0.29, 95% CI 0.11‐0.78) . Similarly, a single‐site pediatric study comparing 20 SOT recipients with CDI and 35 controls found that acid blockade had a protective effect (OR 0.13, 95% CI: 0.02‐0.78), and a pediatric study in intestinal transplant recipients that compared 29 cases with 87 controls found that PPIs were associated with lower rates of CDI (OR 0.06, 95% CI: 0.007‐0.52) . Findings from these studies may have been limited by small sample size, timing of PPI therapy, or other confounders.…”
Section: Discussionmentioning
confidence: 87%
“…5 Similarly, a single-site pediatric study comparing 20 SOT recipients with CDI and 35 controls found that acid blockade had a protective effect (OR 0.13, 95% CI: 0.02-0.78), 12 and a pediatric study in intestinal transplant recipients that compared 29 cases with 87 controls found that PPIs were associated with lower rates of CDI (OR 0.06, 95% CI: 0.007-0.52). 27 Findings from these studies may have been limited by small sample size, timing of PPI therapy, or other confounders. Mechanistically, PPIs (and acid blockade) increase the gastric pH, which may lead to changes in the intestinal microbiome, 28 possibly promoting a more hospitable environment for C difficile to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…partially due to their heavy net state of immunosuppression and multiple pre-and posttransplant events that are detrimental to their gut microbiota. 2,3 Indeed, in intestinal transplantation, the fertile grounds for CDI begin before the transplant procedure. Disorders leading to irreversible intestinal failure, such as Crohn's disease and ulcerative colitis, and clinical interventions, such as enteral feeding, bowel ostomy surgery, and proton pump inhibitors, have all been associated with gut microbiota disruption.…”
mentioning
confidence: 99%
“…Risk factors for recurrent CDI such as advanced age, immunocompromised state, and severe infection at initial presentation are well described in SOT recipients. Intestinal transplant recipients (ITRs) are particularly vulnerable to CDI and recurrent CDI, partially due to their heavy net state of immunosuppression and multiple pre‐ and posttransplant events that are detrimental to their gut microbiota 2,3 . Indeed, in intestinal transplantation, the fertile grounds for CDI begin before the transplant procedure.…”
mentioning
confidence: 99%